2019
DOI: 10.31234/osf.io/d2bxw
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interactions between audition and cognition in hearing loss and aging

Abstract: Understanding spoken language requires transmission of the acoustic signal up the ascending auditory pathway. However, in many cases speech understanding also relies on cognitive processes that act on the acoustic signal. One area in which cognitive processing is particularly striking during speech comprehension is when the acoustic signal is made less challenging, which might happen due to background noise, talker characteristics, or hearing loss. This chapter focuses on the interaction between hearing and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 127 publications
0
4
0
Order By: Relevance
“…In addition, it should be noted that the differences we observed between young and older adults do not in themselves identify the underlying cause of the effect of age on syntactic comprehension. Age-related effects could, in part, be the result of declines in peripheral and central hearing (Rogers & Peelle, in press) or auditory-motor speech processing (Panouillères & Möttönen, 2017). However, in our study, accuracy across the board was relatively high for the older adults (specifically, the older adults’ group average accuracy was above 85% in the experimental conditions and even above 90% in the filler conditions).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it should be noted that the differences we observed between young and older adults do not in themselves identify the underlying cause of the effect of age on syntactic comprehension. Age-related effects could, in part, be the result of declines in peripheral and central hearing (Rogers & Peelle, in press) or auditory-motor speech processing (Panouillères & Möttönen, 2017). However, in our study, accuracy across the board was relatively high for the older adults (specifically, the older adults’ group average accuracy was above 85% in the experimental conditions and even above 90% in the filler conditions).…”
Section: Discussionmentioning
confidence: 99%
“…In a review exploring the contribution of cognition to speech-in-noise listening, listening strategy selection was found to depend upon listener characteristics such as age, hearing status, linguistic competency, educational attainment, and cognitive status [ 87 ]. Metacognitive judgements (i.e., monitoring which the authors define as one’s awareness of cognitive processing) have been found to be largely preserved in older adults relative to younger adults but only to the extent that monitoring does not draw upon executive attention [ 88 ]. Further work is needed, building upon this body of work and the findings of this meta-synthesis, to understand the differential contribution of various listener characteristics on metacognitive knowledge, monitoring, and regulation in the context of HL.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, difficulties understanding speech are one of the most prevalent complaints among older adults, especially in daily listening situations when listening conditions are not ideal (e.g., Abrams and Farrell, 2011 ). Although hearing deficits are a main source of difficulty in speech perception ( Humes et al, 1994 ; Humes, 2021 ), successful speech perception also depends on the interaction of bottom-up hearing related factors and top-down linguistic and cognitive processes ( Sommers, 2005 ; Zekveld et al, 2006 ; Pichora-Fuller, 2008 ; Rogers and Peelle, 2021 ). Furthermore, difficulties in speech perception are also observed among older adults with relatively preserved hearing ( Sommers and Danielson, 1999 ; Fostick et al, 2013 ; Lash et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%